Diagnosis dan Tata Laksana Capsulitis Adhesiva - Amelia Puspita Suhendro (Cermin Dunia Kedokteran, 2023)
Capsulitis adhesiva atau frozen shoulder merupakan gangguan sendi bahu akibat proses peradangan lapisan kapsular sendi glenohumeral yang menyebabkan kekakuan dan nyeri. Kondisi ini relatif umum. Diagnosis melalui anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang. Tatalaksana dilakukan secara non-operatif dan operatif.   Adhesive capsulitis or frozen shoulder is a disorder of the shoulder joint due to an inflammatory process in the capsular layer of the glenohumeral joint, resulting in stiffness and pain. This condition is relatively common. Diagnosis can be made through history, physical examination, and investigations. Management choices are non-operative and operative methods.